Possibilities of Surgical Treatment of Vulva Cancer in the Context of the COVID-19 Pandemic - Sh. Kh. Gantsev; O. N. Lipatov; K. V. Menshikov (Креативная хирургия и онкология)
Background. At the end of 2019, a new coronavirus infection emerged in the People’s Republic of China. On March 11, 2020, the World Health Organization announced the start of the COVID19 pandemic. During 2018, 2068 patients with malignant neoplasms of the vulva were identified, with the majority of patients aged 75–79 years. Surgical treatment is currently the main treatment method for vulva cancer (VC) patients. According to most authors, surgical treatment is the only method providing good longterm results. One of the approaches to reducing the volume of surgical treatment in such patients is the selective biopsy of the sentinel lymph node (SLN).Aim. To apply the method of SLN biopsy in VC patients with the purpose of reducing the amount of surgical treatment and surgical complications, as well as shortening hospital stay in the context of the COVID19 pandemic.Materials and methods. This paper presents the results of surgical treatment of 19 patients with malignant neoplasms of the vulva. All the patients were at risk for a complicated course of COVID19 due to age and concomitant pathologies. In 13 cases, vulvectomy with SLN biopsy was performed. SLN biopsy was performed by radioisotope lymphoscintigraphy.Results and discussion.A decrease in the duration of hospital stay and the absence of surgical complications characteristic of lymphadenectomies were noted.Conclusion. Reducing the duration of hospital stay in the context of the COVID19 pandemic is an urgent task. The method of SLN biopsy in patients with invasive squamous cell carcinoma of the vulva with T1A — T2 was found to be effective, allowing the amount of surgical treatment to be reduced. Vulvectomy accompanied by SLN biopsy is the surgical treatment of choice in the context of strict antiepidemiological measures in the COVID19 pandemic.